(untitled) (Andamios, Revista de Investigación Social, 2011)
The aim of the study was to analyse the doctors’ perceptions of their medical practices in the frontier region of the State of Chiapas, Mexico. A qualitative study was carried out through individual in-depth interviews with working doctors, and were analyzed in accordance with the doctors’ core curriculum and personal knowledge. The study concluded that despite this, this important aspect of training for all health personnel is given little importance in the university curriculum. As a result the individual, his/her suffering and emotions, and the context of his/her condition are forgotten due to the doctor’s emphasis on the physio-biological aspects of the illness. Only through the medical practices these professionals have came to understand that their relationship with the patient is very important for recovery.